Stable tensile recovery strain induced by a Ni4Ti3 nanoprecipitate in a Ni50.4Ti49.6 shape memory alloy fabricated via selective laser melting. (15th October 2021) - Lu, H.Z.; Ma, H.W.; Cai, W.S.; Luo, X.; Wang, Z.; Song, C.H.; Yin, S.; Yang, C.
Abstract: We report a stable tensile recovery strain induced by a Ni4 Ti3 nanoprecipitate in a Ni50.4 Ti49.6 shape memory alloy (SMA) fabricated via selective laser melting (SLM), followed by a discussion on the underlying physical mechanism. In particular, the physical properties, such as morphology and size of the Ni4 Ti3 nanoprecipitate were tailored by heat treatment, namely solid solution and aging treatment, of the SLM-fabricated (SLMed) SMA. The heat-treated SMA exhibited a three-stage phase transformation owing to the larger aspect ratio and smaller size of the Ni4 Ti3 nanoprecipitate; furthermore, it exhibited a larger strain/stress field inside the grain interior region relative to the grain boundary region. The significantly larger endothermic and exothermic enthalpies in the heat-treated SMA relative to the SLMed counterpart were due to the substantial elimination of the dislocation and residual stress generated during SLM, and the lower Ni concentration in the B2 matrix induced by the formation of Ni-rich Ni4 Ti3 nanoprecipitate. In particular, the stress-controlled loading and unloading tests led to a decrease in the endothermic and exothermic enthalpies of the heat-treated SMA. This is ascribed to the formation of stabilized B19′ martensite after the formation of high-density dislocations and enhanced strain/stress field around the coherent Ni4 Ti3 nanoprecipitate during tensile cycles. Interestingly, a stable tensile recovery strain as high as 2.25–3.74% was obtained in the heat-treated SMA during the stress-controlled loading and unloading tests. Fundamentally, this was attributed to the saturation of the dislocations formed at critical tensile cycles, which can be achieved by the dislocation pile-up around the spherical Ni4 Ti3 nanoprecipitate or the dislocation cut-through of the lenticular Ni4 Ti3 nanoprecipitate. Finally, these results can provide significant insights into tailoring the microstructure and functional properties of NiTi SMAs by SLM. Graphical abstract: Image, graphical abstract